2011
DOI: 10.1042/bj20101852
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable HIV-1 group O reverse transcriptase variants with the same fidelity as murine leukaemia virus reverse transcriptase

Abstract: Wild-type HIV-1 group O RT (reverse transcriptase) shows increased thermostability in comparison with HIV-1 group M subtype B RT and MLV (murine leukaemia virus) RT. However, its utility in the amplification of RNA targets is limited by the reduced accuracy of lentiviral RTs compared with oncoretroviral RTs (i.e. MLV RT). The effects of the mutations K65R, R78A and K65R/V75I on the fidelity of HIV-1 group O RTs were studied using gel-based and M13mp2 lacZ forward-mutation fidelity assays. Forward-mutation assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 46 publications
3
54
0
Order By: Relevance
“…In vitro and ex vivo experiments have shown that decreased RNase H activity leads to reduced template switching (55–58). In our assays, based on DNA-dependent DNA synthesis, we found that RNase H-deficient mutants can generate large deletions (and insertions), while these types of errors are rare in RTs with wild-type RNase H activity (22,31). Previous studies showed that RNase H minus HIV-1 RT (i.e.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In vitro and ex vivo experiments have shown that decreased RNase H activity leads to reduced template switching (55–58). In our assays, based on DNA-dependent DNA synthesis, we found that RNase H-deficient mutants can generate large deletions (and insertions), while these types of errors are rare in RTs with wild-type RNase H activity (22,31). Previous studies showed that RNase H minus HIV-1 RT (i.e.…”
Section: Discussionmentioning
confidence: 83%
“…Phage DNA was obtained from all mutant plaques, and the sequence of the reporter gene was determined in all cases. No lac Z mutations were identified after sequencing phage DNA from >20 000 plaques obtained from two to three E. coli electroporations carried out with gapped M13mp2 DNA substrate (31). For each enzyme, mutant plaques were obtained after transfection with the products of four to six gap-filling reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these mutations were developed by random mutagenesis, but the multiple variant E69K/E302R/ W313F/L435G/N454K has lower K m value for T/P than the wild-type MMLV RT (Aresi and Hogrefe 2009). In HIV-1 RT, it was recently reported that the HIV-1 group O RT is more stable than HIV-1 group M (major-typed) RT and is as stable as MMLV RT (Á lvarez et al 2009;Barrioluengo et al 2011). The sequence homology between these two HIV-1 RTs is 21 %, and the amino acid residues essential for the difference in stability have not been identified.…”
Section: Increase In Rt Stability By Introducing Positive Charges By mentioning
confidence: 99%
“…However, without a precise comparison of fidelity and processivity, it is difficult to determine which variant is the most suitable. To address this, further characterization of the thermostable variants generated previously (MM3 and MM4) 8) and in this study (MM7 and MM8) by misincoporation, mispair extension, and primer extension assay 17,18) is currently in progress.…”
mentioning
confidence: 99%